2023
DOI: 10.29333/iji.2023.1627a
|View full text |Cite
|
Sign up to set email alerts
|

Parental Involvement and Student Achievement: A Meta-analysis of Publications in the Scopus Database

Abstract: This study aims to analyze the effect size correlation between parental involvement and student achievement. This research uses quantitative method with metaanalysis approach. The study subjects were 27 publications of relevant research results that discussed the variables of parental involvement and student achievement. Research data collection is carried out through documentation techniques by collecting research publications with criteria including publications that must come from Scopus indexed journals. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Turning to research on the children's achievement and mathematical outcomes which the parents' values and communication are aimed at in this study, reviews and metaanalyses (Boonk et al, 2018;Hill & Tyson, 2009;Jeynes, 2007;Sujarwo & Herwin, 2023;Wilder, 2014) demonstrate connections between parental involvement and children's academic achievement. In a literature review on parental involvement and mathematic outcomes, Fiskerstrand (2022) identified several studies that connected children's motivations for mathematics with parents' values.…”
mentioning
confidence: 99%
“…Turning to research on the children's achievement and mathematical outcomes which the parents' values and communication are aimed at in this study, reviews and metaanalyses (Boonk et al, 2018;Hill & Tyson, 2009;Jeynes, 2007;Sujarwo & Herwin, 2023;Wilder, 2014) demonstrate connections between parental involvement and children's academic achievement. In a literature review on parental involvement and mathematic outcomes, Fiskerstrand (2022) identified several studies that connected children's motivations for mathematics with parents' values.…”
mentioning
confidence: 99%